2019
DOI: 10.1111/vox.12878
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ABO isoagglutinin titres by three different methods: tube haemagglutination, micro‐column agglutination and automated immunohematology analyzer based on erythrocyte‐magnetized technology

Abstract: Background and Objectives ABO isoagglutinin titre is important for evaluating and monitoring ABO-incompatible (ABOi) stem cells or solid organ transplantations. There are several methods to measure the titre level, including the tube haemagglutination method, micro-column agglutination and erythrocyte-magnetized technology (EMT). However, few studies have reported isoagglutinin measured by EMT. Here, we compared the isoagglutinin titre of normal individuals obtained by an automated instrument with that obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
1
15
2
Order By: Relevance
“…Even on comparison of card method with TT and EMT, agreement results were comparable in case of IgM but low in IgG. 17 Taking all BGs together, our study gave more than 90% results of IgG as well as IgM within one titer difference.…”
Section: Discussionmentioning
confidence: 50%
“…Even on comparison of card method with TT and EMT, agreement results were comparable in case of IgM but low in IgG. 17 Taking all BGs together, our study gave more than 90% results of IgG as well as IgM within one titer difference.…”
Section: Discussionmentioning
confidence: 50%
“…Shim et al. [38] compared three methods of antibody titration using 40 samples and found that the median IgM and IgG titres were higher by CAT with the a better agreement for IgM than for IgG. In the present study, median titres were determined separately for IgM and IgG for anti‐A and anti‐B as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Similarly, in the present study, the correlation was found to be strong or very strong between CTT (1+) and CAT (1+, 2+) for both IgG and IgM of both anti-A and anti-B isoagglutinins. Shim et al compared three methods of antibody titration using 40 samples and found that median ABO IgM and IgG titres of all blood groups obtained by the erythrocytemagnetized technology method were higher than those obtained by the conventional tube haemagglutination and micro-column agglutination [36]. They found that the agreement between the methods was comparable in case of IgM but low in case of IgG.…”
Section: Discussionmentioning
confidence: 99%